新加坡华语单音节形容词重叠研究 = A study of monosyllabic adjective reduplication in Singapore Mandarin Chinese - 蔡明惠 Chua, Joan Ming Hui (Nanyang Technological University, 2023)
近年来，普通话和新加坡华语这两个汉语变体的差异引起不少学者的关注。 许多学者指出新加坡华语在语法、词汇和语音等方面所呈现出来的特色。尽管前人 研究包括形容词及其重叠的现象，但现有讨论以举例为主，缺少以自然语料为基础 的系统且全面的考察。为填补这一研究空缺，本研究试图以新加坡华语媒体和网络 为语料来源，系统且全面地调查新加坡华语单音节形容词重叠的使用情形，并比较 它们与普通话的不同。本文从郑怀德与孟庆海（2003）编著的《汉语形容词用法词 典》收录163个单音节形容词为研究对象。第一章将综述前人对单音节形容词重叠的 研究。第二章介绍本研究的意义以及研究方法。第三章则探析新加坡华语单音节词 的重叠范围。第四章主要说明新加坡华语单音节形容词重叠的语法功能和语法意义。 第五章将对本研究做个总结，并指出文章的不足之处。In recent years, the differences between the two Chinese varieties, Putonghua and Singapore Mandarin Chinese, have sparked the interest of many researchers. Many researchers pointed out that Singapore Mandarin Chinese is unique from Putonghua in terms of grammar, vocabulary, and pronunciation. Although previous studies include adjectives and their reduplication, the existing discussions are primarily example-based and lack natural language data which would otherwise conform to a systematic and comprehensive investigation. To fill this research gap, this study uses Singapore Mandarin Chinese media and internet sources to carry out a detailed investigation of the usage of Singapore Mandarin Chinese monosyllabic adjective reduplication and how they differ from Putonghua. This thesis has collected 163 monosyllabic adjectives from Hanyu Xingrongci Yongfa Cidian as research sample. The first chapter reviews past studies related to monosyllabic adjective reduplication. The second chapter states the significance of the study as well as the research method. The third chapter explores the scope of monosyllabic adjective reduplication in terms of its reduplication ability and reduplication form. The fourth chapter mainly explains the syntax of monosyllabic adjective reduplication. The fifth chapter concludes the paper and touches on the flaws, which will require future research.